Absolute Chronology of Megiddo, Israel, in the Late Bronze and Iron Ages: High-Resolution Radiocarbon Dating. Issue 1 (2014) - Toffolo, Michael B; Arie, Eran; Martin, Mario A S; Boaretto, Elisabetta; Finkelstein, Israel
Abstract : Megiddo (Israel) is a key site for the study of the stratigraphy, chronology, and history of the Bronze and Iron ages in the Levant. The article presents a Bayesian chronological model for seven ceramic typology phases and 10 stratigraphic horizons at this site, covering the Late Bronze and much of the Iron Age. The model is based on 78 samples, which provided 190 determinations—the most thorough set of radiocarbon determinations known so far in a single site in the Levant. This set of data provides a reliable skeleton for the discussion of cultural processes and historical events in the region and beyond, including the periods of the Egyptian Empire in Canaan and the Northern Kingdom of Israel.